Criminal Protection of the Environment of the Republic of Serbia in the Light of the New EU Directive From 2024 - Simović, Marina (Glasnik Advokatske komore Vojvodine, 2026)
The system of environmental criminal offenses under the Criminal Code of Republika Srpska provides for several criminal offenses against the environment, in their basic or qualified forms, together with the penalties prescribed for their perpetrators. Given the need for efficient and high-quality criminal law protection of the environment as a whole, or of its individual elements, it is necessary continuously to update existing legislative solutions with a view to improving them, both from the perspective of the needs of modern crime suppression policy and, even more importantly, because of the emergence of new and different forms of damaging or endangering the environment. This is also supported by the need to harmonize national criminal law systems with relevant international standards. In this paper, the author analyzes the new solutions contained in the 2024 European Union Directive on the protection of the environment through criminal law from the perspective of their implementation in the criminal legislation of Republika Srpska.